Compact Dual-Band Planar Inverted-e-Shaped Antenna Using Defected Ground Structure - Wen Piao Lin; Dong-Hua Yang; Zong-De Lin (International Journal of Antennas and Propagation)
This paper presents a novel dual-band planar inverted-e-shaped antenna (PIEA) using defected ground structure (DGS) for Bluetooth and wireless local area network (WLAN) applications. The PIEA can reduce electromagnetic interferences (EMIs) and it is constructed on a compact printed circuit board (PCB) size of 10 × 5 × 4 mm3. Experimental results indicate that the antenna with a compact meandered slit can improve the operating impedance matching and bandwidths at 2.4 and 5.5 GHz. The measured power gains at 2.4 and 5.5 GHz band are 1.99 and 3.71 dBi; antenna efficiencies are about 49.33% and 55.23%, respectively. Finally, the good performances of the proposed antenna can highly promote for mobile device applications.